Evolution - Stonebarger, Bill (Wisconsin : Hawkhill Video, 1998)
This video teaches about science, technology and society from all three of these angles - Time, Space and Spirit
Editor, Bill Stonebarger, Michael Stonebarger
Keywords: Evolution